(untitled) (Colloquia Comparativa Litterarum, 2025)
In this article, I continue my observation and discussion of West European Literature within the context of Comparative Literature taken up in an earlier paper. The focus is on the subject matter’s two general aspects: as a research field, and as an academic discipline. When reviewed as a research field, attention has been given to the crises and rethinking of Comparativism, to national and international projects and works in the yet new century, to their juxtaposition and conceptual common places. In discussing it as an academic discipline, I have dealt with practical issues of the syllabus distribution and teaching, and the studying of literary phenomena in translation and discontinuity with an emphasis on their reception and transformation in the host environment.